KAJIAN ATAS PERLAKUAN AKUNTANSI TERHADAP SKEMA PERDAGANGAN EMISI (EMISSION TRADING SCHEME) PELAJARAN DARI UNI EROPA DAN AUSTRALIA - Sujai, Mahpud (Badan kebijakan Fiskal, 2010)
Governments have responded the emission trading scheme in a variety of ways and there is no exact similarities between regions. This essay try to express accounting implication of carbon markets under the emission trading scheme. In regards to accounting and reporting issues, this essay try to review the measurement and recognition criteria of emission allowances as assets and liability once emission are emitted depending on permits held, especially in the context of Indonesia compare with other best practices countries such as European Union and Australia. This essay also explores the possibilities of accounting implementation on emission trading scheme in Indonesia since it is not implemented yet